2015
DOI: 10.1242/jeb.116558
|View full text |Cite
|
Sign up to set email alerts
|

Developmental thermal plasticity of prey modifies the impact of predation

Abstract: Environmental conditions during embryonic development can influence the mean expression of phenotypes as well as phenotypic responses to environmental change later in life. The resulting phenotypes may be better matched to their environment and more resilient to environmental change, including human-induced climate change. However, whether plasticity does improve success in an ecological context is unresolved. In a microcosm experiment, we show that developmental plasticity in embryos of the frog Limnodynastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Our analysis revealed that the degree of Melanoplus femurrubrum stress response to perceived predation risk varied with rearing temperature. This is consistent with growing evidence from aquatic species that the nature and degree of plasticity in prey responses due to predation stress is dependent upon the thermal environment prey experience during their development (Culler et al 2014, Matassa and Trussell 2015, Seebacher and Grigalchik 2015.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our analysis revealed that the degree of Melanoplus femurrubrum stress response to perceived predation risk varied with rearing temperature. This is consistent with growing evidence from aquatic species that the nature and degree of plasticity in prey responses due to predation stress is dependent upon the thermal environment prey experience during their development (Culler et al 2014, Matassa and Trussell 2015, Seebacher and Grigalchik 2015.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with growing evidence from aquatic species that the nature and degree of plasticity in prey responses due to predation stress is dependent upon the thermal environment prey experience during their development (Culler et al. , Matassa and Trussell , Seebacher and Grigalchik ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Experiments examining additional stressors like toxins, pollutants or rising temperature, layer on these stressors by factorially combining them with levels of predator cues [e.g. [30][31][32][33][34].…”
Section: State-dependence: Blending Analyses Of Plasticity and Local mentioning
confidence: 99%